Forms of Parenting and Influencing Factors in the Cultivation of the Spirit of Entrepreneurship in Children with Deafblindness in the Mojokerto Region - Nyuherno Aris Wibowo; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (Pusat Riset dan Inovasi Nasional, 2023)
This research design uses qualitative research methods with a case study approach. The key informants of this research are parents of children with hearing impairment in Mojokerto. From the results of data collection conducted by semi-structured interview method, the following research results have been obtained. The factors that influence parenting in instilling the spirit of entrepreneurship are a limited time to study business because of the busy school time, and the talent that supports the child himself. The impact of the parenting pattern given even though children with disabilities appear the formation confident, independent, able to socialize with the environment, and unyielding to learn business.